FEMTOSECOND LASER-ASSISTED ANTERIOR LAMELLAR KERATOPLASTY: PILOT CLINICAL TRIAL - B. E. Malyugin (Офтальмохирургия, 2015)
Purpose. To work out a technology of a femtosecond laser assisted anterior lamellar keratoplasty and evaluate its safety and clinical efficiency.Material and мethods. We report 13 cases of femtosecond laserassisted anterior lamellar keratoplasty. Both circular trepanation and lamellar dissection (80% of the corneal thickness) were performed with the IntraLase FS 60 kHz (AMO). Lamellar cut settings for the donor cornea were: spot/line separation 4/4μm, energy 1μJ; for the recipient 4/4μm and 2μJ, respectively. Eyes of 13 patients (11 with keratoconus, 2 with superficial corneal scarring) in the mean age 30.3±9.5 years were observed up to 2 year s after the surgery.Results. All corneal grafts were transparent, with the mean endothelial cell loss at 12 months equal to 3.5%. Evaluation of biomechanical properties of patients’ corneas 1 year after the surgery showed a reliable improvement of the CRF and CH meanings, comparable to preoperative data, from 5.7±1.28 and 6.92±1.32mmHg to 10.92±1 and 10.61±1.3mmHg (p<0.001), respectively, which correlates with the rates of normal cornea. Sutures were removed 6 months after surgery. The mean postoperative astigmatism at 12 months was 4.7±1.5 D. The mean UCVA at 12 months was 0.1±0.02 and the BCVA was 0.22±0.07. After 2 years the values were 0.2±0.03 and 0.3±0.05, respectively. The highest BCVA was achieved0.4 in 2 cases at 12 months.Conclusions. The obtained low postoperative visual acuity is explained, apparently, by irregularities of the donor-recipient interface and a pronounced light scattering occurred in it which leads to a reduction of the retinal image quality.